Membrane fouling mitigation with 3D/4D printed feed spacers - Koo, Jing Wee (Nanyang Technological University, 2022)
Membrane fouling is a major setback for membrane filtration processes because it causes problems such as increased energy consumption or decreased water permeate quality. Although it is inevitable, there are various means of mitigating membrane fouling. Within the spiral wound module, improving the membrane and feed spacer layers are some approaches of slowing down the fouling process. However, traditional ways of fabricating membranes and spacers faced several limitations, especially when it comes to the physical structure of the spacer and membrane. Conventional heat extrusion methods could only fabricate mesh spacers, of which studies have shown has inherent dead zones especially around the filament nodes. These dead zones can encourage membrane fouling. Membrane modification methods such as micro-moulding and nanoimprint lithography successfully introduced patterned structures on the membrane surface, but they often caused a decrease in membrane permeability due to the additional coatings. To further improve the membrane and spacer layers, there is a need for a new fabrication method to overcome these limitations. Additive manufacturing, with its great flexibility in design and material customization, could be a good alternative fabrication method for the manufacturing of membranes and spacers. A detailed literature review on membrane fouling control and 3D printing showed the potential for this interdisciplinary study. While there were many successful works on 3D printed spacers, there seems to be several fundamental concerns with 3D printed membranes. The current state-of-the-art 3D printing techniques do not have the inherent printing resolution to fabricate the fine membrane pores. As such, 3D printed membranes were typically fabricated by hybrid additive manufacturing, which involved a second process to fabricate membrane pores. From this perspective, the significance of 3D printing is in question because the most important feature of a membrane is not directly controlled by 3D printing. There is a lack of proper standards to evaluate 3D printed membranes, and therefore 3D printing was deemed premature at this stage for further experimental studies. Therefore, this thesis will focus more on employing 3D printing to fabricate membrane spacers with innovative structures and properties that can help mitigate membrane fouling instead. Drawing inspiration from previous studies on sinusoidal flow channels, a new sinusoidal spacer design was investigated. By introducing straight and slanted transverse filaments, the sinusoidal channels can be fabricated as a standalone membrane spacer layer. The novel spacer demonstrated superior membrane fouling mitigation capabilities by decreasing inorganic fouling by up to 15% and biofouling by up to 11% as compared to a conventional mesh spacer. Although it also resulted in greater channel pressure loss, the energy saved from reduced membrane fouling far exceeded the increased energy consumption. Optical coherence tomography and membrane autopsy revealed the fouling pattern caused by the sinusoidal spacers, and it showed how the vortices caused by the sinusoidal channel reduced membrane fouling in certain local areas. 4D printing was also used to fabricate innovative dynamic spacers. Novel piezoelectric material and additives were used to print piezoelectric spacers capable to vibrating under the influence of an alternating current. These vibrations successfully increased the critical flux by up to 16% as compared to a static spacer. They also slowed down membrane fouling by up to 42% when additives were added to the spacer. Optical coherence tomography analysis revealed that the in-situ vibrations significantly changed the fouling pattern, where less foulants were observed around the vibrating transverse filaments. Overall, these favorable results have contributed as the first fundamental work in the study of piezoelectric spacers.